Production Planning in the Nigerian Detergent Producing Firm: A Linear Programming Method - Osuolale, Misbaudeen Olatunde (My University, 2016)
This study applied Linear programming technique to production planning problem of Detergent producing company in Nigeria. Linear Programming (LP) model was formulated. Data were analysed based on manpower cost, production cost on regular and overtime basis, overhead cost and work force, inventory cost, the materials cost, which were assumed to be proportion to the number/magnitude of the outputs. The generated LP model was solved using software named LINGO 11.0 software a member of Linear Interactive Numerical and Discrete Optimizer (LINDO) software. The results of the model revealed the awareness about a general apathy towards the use of linear programming and other mathematical or analytical techniques in production planning. Their planning attention is focused rather on the procurement of raw materials and the expansion of production capacity thus, the resultant effect of this is inadequate use of available productive capacity, and it also suggested that the monthly total cost of production could be reduced up to N 2 million on an average. The sensitivity analysis showed that the results have a wide range of feasibility showing various adjustments that could be made in production planning for achieving their objectives. This analysis has shown that linear programming techniques can improve production planning performance thus, recommended as the appropriate/veritable planning tool for managers to apply in their various organizations.
Keywords: Linear Programming; Production Planning; LINDO software; Inventory level